An oval large flowered raised paint and a preparation method thereof

CN122958889APending Publication Date: 2026-10-23SHENGXIANG IND (SHANGHAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611255039.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

花纹定型能力差:若涂料的屈服应力和触变性不足,在拉毛施工后,形成的椭圆花纹容易在重力作用下发生塌陷、流挂,导致花纹扁平,无法保持立体的大花效果;

Benefits of technology

1、本申请通过羟乙基纤维素与锂基膨润土的协同配合,构建了拉毛涂料的基础流变骨架,羟乙基纤维素提供基础粘度和保水性,使涂料在施工过程中保持适当的流动性和开放时间;锂基膨润土提供触变性和屈服应力,使涂料在施工后能够迅速恢复结构粘度,支撑立体花纹不塌陷,二者按特定比例复配后,既保证了椭圆大花纹的定型能力,又避免了因单一增稠组分过量导致的粘度过高、施工困难以及表面粗糙问题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of building coatings, in particular to an oval large-flower napping coating and a preparation method thereof. The raw material composition of the coating is as follows: 80-120 parts of water, 1.5-4 parts of hydroxyethyl cellulose, 1.5-4 parts of lithium-based bentonite, 3-8 parts of a dispersing agent, 4-10 parts of a defoaming agent, 240-320 parts of an acrylic elastic emulsion, 8-12 parts of titanium white, 480-640 parts of quartz powder, 3-8 parts of a film-forming aid, 15-30 parts of ethylene glycol, 1-4 parts of a neutralizing agent, 1-3 parts of a polyurethane associated thickening agent, 1-3 parts of a hydrophobically modified associated alkali-swellable thickening agent and 1-5 parts of a preservative. The hydroxyethyl cellulose and the lithium-based bentonite are used to cooperatively build a rheological skeleton, two kinds of thickening agents are used, and a preparation process of segmented variable-speed stirring and two-time addition of the defoaming agent is combined, so that the napping coating has excellent pattern setting capacity and elastic crack resistance, and the formed oval convex surface is smooth and crack-free.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of architectural coatings technology, and in particular to an elliptical large-pattern textured coating and its preparation method. Background Technology

[0002] Textured paint is a thick-paste textured paint widely used in interior and exterior wall decoration. By using specific construction tools, such as textured rollers, to scrape or roll on the wall surface, textured paint can create a three-dimensional textured surface. It can not only enrich the decorative effect of the wall, but also effectively cover up minor defects in the substrate. Among them, oval large flower is a popular texture form. Its flower shape is round and full, with distinct layers, and has excellent visual appeal.

[0003] However, achieving the desired large elliptical floral texture places extremely high demands on the rheological properties of the coating.

[0004] Textured coatings in related technologies typically suffer from the following defects during preparation and application: Poor pattern retention: If the yield stress and thixotropy of the coating are insufficient, the elliptical pattern formed after roughening is prone to collapse and sagging under gravity, resulting in a flat pattern that cannot maintain a three-dimensional large pattern effect. Insufficient crack resistance: In order to form a thick three-dimensional pattern, the coating is usually thick. During the drying and curing process, due to moisture evaporation and volume shrinkage, as well as thermal expansion and contraction caused by changes in ambient temperature, ordinary coatings are very prone to micro-cracks or even through-cracks, affecting the decorative aesthetics and wall protection.

[0005] Therefore, providing a method that combines excellent elasticity and crack resistance with the ability to stably form large elliptical floral patterns is a problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0006] In order to ensure the excellent elasticity and crack resistance of elliptical textured coating while maintaining the elliptical texture, this application provides an elliptical textured coating and its preparation method.

[0007] Firstly, this application provides an elliptical large-pattern textured coating, which adopts the following technical solution: An elliptical floral textured coating, characterized in that: by weight, the raw material composition includes: 80-120 parts water; Hydroxyethyl cellulose 1.5-4 parts; 1.5-4 parts lithium-based bentonite; 3-8 parts dispersant; 4-10 parts of defoamer; 240-320 parts of acrylic elastic emulsion; 8-12 parts titanium dioxide; 480-640 parts of quartz powder; 3-8 parts of film-forming aid; 15-30 parts of ethylene glycol; Neutralizing agent 1-4 parts; 1-3 parts of polyurethane associative thickener; 1-3 parts of hydrophobically modified associative alkali-swellable thickener; Preservative 1-5 parts.

[0008] By adopting the above technical solution, this invention uses hydroxyethyl cellulose and lithium-based bentonite as the basic rheological framework, combined with acrylic elastic emulsion to provide elastic film-forming ability, and introduces a dual thickening system of polyurethane associative thickener and hydrophobically modified associative alkali-swelling thickener, to achieve precise control of the rheological properties of textured coatings. Hydroxyethyl cellulose provides basic viscosity and water retention, while lithium-based bentonite provides thixotropy and yield stress. The synergistic effect of the two enables the coating to quickly form a stable three-dimensional pattern after application, avoiding collapse and sagging. At the same time, the acrylic elastic emulsion forms a continuous elastic network after drying and film formation, effectively absorbing drying shrinkage stress and preventing cracking. The dual thickening system provides gradient viscosity response at different shear rates, ensuring both leveling during application and pattern setting ability. Ultimately, the textured coating possesses excellent pattern setting ability, elastic crack resistance, and surface smoothness.

[0009] Preferably, the weight ratio of the hydroxyethyl cellulose to the lithium-based bentonite is 1:0.6-1.6.

[0010] By adopting the above technical solution, the weight ratio of hydroxyethyl cellulose to lithium-based bentonite is limited to the range of 1:0.6-1.6, so that the two form an optimal synergistic ratio. When the ratio is within this range, the basic viscosity provided by hydroxyethyl cellulose and the thixotropy provided by lithium-based bentonite are balanced, which can ensure that the coating has sufficient yield stress to support the three-dimensional pattern, and can avoid the problem of excessive viscosity and construction difficulties caused by excessive bentonite.

[0011] Preferably, the weight ratio of the polyurethane associative thickener to the hydrophobic modified associative alkali-swellable thickener is 1:0.5-1.5.

[0012] By adopting the above technical solution, the weight ratio of polyurethane associative thickener to hydrophobically modified associative alkali-swellable thickener is limited to the range of 1:0.5-1.5, enabling the dual thickening system to achieve optimal rheological coverage across the entire shear rate domain. The polyurethane associative thickener mainly provides viscosity at high shear rates, improving the leveling properties during application; the hydrophobically modified associative alkali-swellable thickener mainly provides viscosity at medium and low shear rates, enhancing the pattern setting ability. When the ratio is within this preferred range, the two thickeners work synergistically, ensuring smooth leveling of the coating during application, preventing the pattern from collapsing under gravity, and resulting in a smooth and defect-free coating surface.

[0013] Preferably, the acrylic elastic emulsion comprises 260-300 parts by weight; and the quartz powder comprises 520-600 parts by weight.

[0014] By adopting the above technical solution, within this dosage range, the acrylic elastic emulsion can form a continuous and dense elastic film-forming network, fully encapsulating the quartz powder particles. This ensures both the elasticity and crack resistance of the coating, as well as its hardness and wear resistance. When the emulsion dosage is too low or the quartz powder dosage is too high, the coating is prone to cracking; when the emulsion dosage is too high, the coating hardness is insufficient, and the pattern is prone to collapse.

[0015] Preferably, the film-forming aid is selected from any one of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, dipropylene glycol butyl ether, and propylene glycol phenyl ether.

[0016] By adopting the above technical solutions, all three film-forming aids can effectively reduce the minimum film-forming temperature of acrylic elastic emulsions and promote the full fusion of emulsion particles into a film at room temperature. Among them, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate has excellent film-forming efficiency and hydrolytic stability; dipropylene glycol butyl ether has good volatility rate balance and wettability; and propylene glycol phenyl ether has a high boiling point and low volatility rate, making it suitable for thick coating film formation. All three film-forming aids can achieve the technical effects of this invention and can be flexibly selected according to the actual construction environment temperature.

[0017] Preferably, the dispersant is selected from any one of polycarboxylate dispersants, polyacrylate dispersants, and acrylic-maleic anhydride copolymer salt dispersants.

[0018] By adopting the above technical solutions, all three types of dispersants can effectively disperse titanium dioxide and quartz powder, prevent pigment and filler agglomeration, and improve the hiding power and workability of coatings. Polycarboxylate dispersants have excellent dispersion efficiency and viscosity reduction effect; polyacrylate dispersants have wide pH adaptability; and acrylic acid-maleic anhydride copolymer salt dispersants have special anchoring ability for inorganic fillers. All three types of dispersants can achieve the technical effects of this invention and can be flexibly selected according to the characteristics of the pigment and filler system.

[0019] Secondly, this application provides a method for preparing an elliptical large-flower textured coating, using the following technical solution: S1. Mix water, hydroxyethyl cellulose and lithium-based bentonite to form a basic slurry; S2. Under stirring, add dispersant, first part defoamer accounting for 50-70% of the total amount of defoamer, acrylic elastic emulsion, titanium dioxide and quartz powder to the base slurry, and disperse at 1800-2500 r / min for 18-22 min. S3. Adjust the stirring speed to 800-1200 r / min, and add the film-forming aid and ethylene glycol; S4. Add the neutralizing agent while stirring to adjust the pH; S5. Add the remaining amount of the second part of the defoamer and disperse and defoam at 800-1200r / min for 3-7min. S6. Add polyurethane associative thickener and hydrophobically modified associative alkali-swellable thickener, and stir at 800-1200 r / min for 8-12 min. S7. Add preservative, stir and mix for 2-3 minutes, cool to 25℃, and obtain the elliptical large-flower textured coating.

[0020] By adopting the above technical solution, the preparation method of the present invention employs a segmented variable-speed stirring strategy: in step S2, pigments and fillers are dispersed at a high speed of 1800-2500 r / min to ensure that titanium dioxide and quartz powder are fully dispersed; in steps S3-S7, subsequent operations are carried out at a medium speed of 800-1200 r / min to avoid foaming of the emulsion and excessive shearing of the thickener caused by high-speed stirring. At the same time, the defoamer is added in two parts: the first part of the defoamer is added in step S2 to suppress the generation of bubbles during the high-speed dispersion stage; the second part of the defoamer is added in step S5 to defoam after film formation, ensuring that the final product is free of bubble defects. This process effectively solves the problem of difficult elimination of bubbles in high-viscosity thick-film coatings.

[0021] Preferably, the acrylic elastic emulsion is added after the first portion of the defoamer is added and before the titanium dioxide is added.

[0022] By adopting the above technical solution, the timing of adding the acrylic elastic emulsion is limited to after the first defoamer and before titanium dioxide and quartz powder. This ensures that the emulsion is fully and evenly mixed with the base slurry before the pigments and fillers are added. The emulsion itself has a wetting and dispersing effect, which can assist the dispersion of subsequent pigments and fillers and improve the dispersion efficiency. At the same time, adding the emulsion in advance can avoid the viscosity change and secondary foaming problems caused by adding it later.

[0023] In summary, this application has the following beneficial effects: 1. This application constructs the basic rheological framework of textured coating through the synergistic combination of hydroxyethyl cellulose and lithium-based bentonite. Hydroxyethyl cellulose provides basic viscosity and water retention, enabling the coating to maintain appropriate fluidity and open time during construction. Lithium-based bentonite provides thixotropy and yield stress, enabling the coating to quickly recover structural viscosity after construction, supporting the three-dimensional pattern without collapsing. When the two are compounded in a specific ratio, it not only ensures the shaping ability of large elliptical patterns, but also avoids problems such as excessive viscosity, construction difficulties and surface roughness caused by excessive amount of a single thickening component. 2. This application achieves rheological coverage across the entire shear rate domain by introducing a dual thickening system of polyurethane associative thickener and hydrophobically modified associative alkali-swellable thickener. The polyurethane associative thickener provides viscosity at high shear rates, improving leveling and coatability during application; the hydrophobically modified associative alkali-swellable thickener provides viscosity at medium and low shear rates, enhancing the pattern's setting ability and anti-sagging properties. When the two thickeners are compounded in a specific ratio, they provide a gradient viscosity response at different application stages, ensuring smooth application, pattern stability, and a smooth, defect-free coating surface. This effectively solves the problem that traditional single thickening systems cannot simultaneously achieve both leveling and setting properties. 3. This application constructs a crack-free film-forming system under high PVC conditions by combining acrylic elastic emulsion with film-forming aids. With the assistance of film-forming aids, the acrylic elastic emulsion forms a continuous and dense elastic film-forming network at room temperature. This network can effectively absorb drying shrinkage stress and thermal expansion and contraction stress, preventing crack formation. At the same time, the antifreeze and wetting effects of ethylene glycol ensure the storage stability and workability of the coating in low-temperature environments. 4. The preparation method of this application effectively solves the problem of preparing high-viscosity thick-film coatings through segmented variable-speed stirring and the process design of adding defoamer in two stages. The high-speed dispersion in step S2 ensures that pigments and fillers are fully dispersed, and the medium-speed stirring in steps S3-S7 avoids emulsion foaming and excessive shearing of the thickener. The defoamer is added in two stages, one during the dispersion stage and the other after film formation, to suppress bubble generation and eliminate existing bubbles, respectively. At the same time, the reverse dispersion process of adding acrylic elastic emulsion after the defoamer and before the pigments and fillers utilizes the wetting and dispersing ability of the emulsion to assist in the dispersion of pigments and fillers, thereby improving the dispersion uniformity. Detailed Implementation

[0024] The present application will be further described in detail below with reference to the embodiments. Example

[0025] Examples 1-5 The raw materials and dosages of an elliptical large-pattern textured coating are shown in Table 1 below: Table 1: Components and their weights (kg) of the raw materials used in Examples 1-5

[0026] In the table above, the hydroxyethyl cellulose is designated as G Pharm and was purchased from Ashland. Lithium-based bentonite was purchased from Shanghai Jiachen Chemical Co., Ltd. The defoamer was Blackburn Dispelair CF 246, purchased from Guangzhou Siteyuan Chemical Co., Ltd. The acrylic elastic emulsion, model Archsol 8119, was purchased from Wanhua Chemical Group Co., Ltd. The titanium dioxide, model R-996, was purchased from Wuhan Jiyesheng Chemical Co., Ltd. The quartz powder, grade 400 mesh, was purchased from Zhonghai Xingrui (Beijing) Technology Co., Ltd. The neutralizing agent, model AMP-95, was purchased from Guangzhou Meishi Chemical Co., Ltd. The polyurethane associative thickener, model HY-2020, was purchased from Shanghai Huiyan New Materials Co., Ltd. The hydrophobically modified associative alkali-swellable thickener, model TT-935, was purchased from Shenzhen Winova Chemical Materials Co., Ltd. The preservative was model 2550 and was purchased from Kaiyin Chemical Co., Ltd. In Examples 1, 4, and 5, the film-forming aid was 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, purchased from Hubei Shishun Biotechnology Co., Ltd.; the dispersant was a polycarboxylate dispersant, model SN-5040, purchased from Tairunding (Guangzhou) New Materials Co., Ltd. In Example 2, the film-forming aid was dipropylene glycol butyl ether, purchased from Nanjing Zhongchun Biotechnology Co., Ltd.; the dispersant was a polyacrylate dispersant, model WD-N55, purchased from Zhejiang Humo Polishing Abrasive Manufacturing Co., Ltd. In Example 3, the film-forming aid was propylene glycol phenyl ether, purchased from Liaoning Kelong Fine Chemical Co., Ltd.; the acrylic acid-maleic anhydride copolymer salt dispersant was sodium maleic acid-acrylic acid copolymer, purchased from Shandong Taihe Technology Co., Ltd.

[0027] An elliptical floral textured coating is prepared using the following steps: S1. Mix water, hydroxyethyl cellulose and lithium-based bentonite for 5 minutes to form a basic slurry; S2. Under stirring, add dispersant, first part defoamer accounting for 50% of the total amount of defoamer, acrylic elastic emulsion, titanium dioxide and quartz powder to the base slurry, and disperse at 2000 r / min for 20 min. S3. Adjust the stirring speed to 1000 r / min, and add the film-forming aid and ethylene glycol; S4. While stirring, add the neutralizing agent to adjust the pH to 8.0-9.0; S5. Add the remaining second part of the defoamer (accounting for 50% of the total amount of defoamer), and disperse and defoam at 1000 r / min for 5 min; S6. Add polyurethane associative thickener and hydrophobically modified associative alkali-swellable thickener, and stir at 1000 r / min for 10 min. S7. Add preservative, stir and mix for 2 minutes, and cool to 25°C to obtain the elliptical large-flower textured coating.

[0028] Comparative Example 1 A texturing coating differs from Example 1 in that the low-viscosity hydroxyethyl cellulose is replaced with high-viscosity hydroxyethyl cellulose, model M Pharm, with a viscosity of 4500–6500 mPa·s. The remaining components and preparation method are the same as in Example 1.

[0029] Comparative Example 2 A texturing coating differs from Example 1 in that lithium-based bentonite is replaced with sodium-based bentonite, which was purchased from Wuhan Jiyesheng Chemical Co., Ltd., while the remaining components and preparation method are the same as in Example 1.

[0030] Comparative Example 3 An elliptical large-flower textured coating differs from Example 1 in that the dual thickening system of polyurethane associative thickener and hydrophobically modified associative alkali-swellable thickener is replaced by using only 4.5 parts of polyurethane associative thickener. The remaining components and preparation method are the same as in Example 1.

[0031] Comparative Example 4 An elliptical large-flower textured coating differs from Example 1 in that the dual thickening system of polyurethane associative thickener and hydrophobic modified associative alkali-swellable thickener is replaced by using only 4.5 parts of hydrophobic modified associative alkali-swellable thickener. The remaining components and preparation methods are the same as in Example 1.

[0032] Comparative Example 5 An elliptical large-flower textured coating differs from Example 1 in that: in step S2, the timing of adding the acrylic elastic emulsion is adjusted to be added after the addition of titanium dioxide and quartz powder; the remaining components and preparation method are the same as in Example 1.

[0033] Performance testing The following properties were tested for the elliptical large-pattern textured coating: container condition, paint film appearance, water resistance (96h), alkali resistance (48h), tensile strength / MPa, and elongation at break / %: referring to the JG / T 172-2014 standard "Elastic Building Coatings". Viscosity: The viscosity / KU of the elliptical large-pattern textured coating was tested in accordance with GB / T 9269-2009 "Determination of viscosity of coatings - Stormer viscometer method"; Surface roughness inspection: Referring to the definition of Ra in GB / T 3505-2009 "Geometric Specifications for Products (GPS) - Terminology, Definitions and Surface Structure Parameters of Surface Structure Profile Method", the surface roughness parameter Ra (μm) of the paint film is inspected using a profile measuring instrument that conforms to GB / T 6062-2009.

[0034] Crack rating: After applying the coating to a calcium silicate board and curing it at 25°C for 24 hours, visually inspect the surface for cracks. Ratings are given from 1 to 5, where 5 indicates no surface cracks and 1 indicates severe cracking. Pattern three-dimensionality: The height of the paint film protrusion (mm) was tested using a laser profilometer conforming to GB / T 33523.3-2017.

[0035] Test samples corresponding to Examples 1-5 above were extracted, and the average value of the test results was recorded in Table 2 below.

[0036] Table 2: Performance Test Results of Examples 1-5

[0037] As shown in Table 2, the elliptical textured coatings prepared in Examples 1-5 exhibit excellent overall performance, all meeting the technical requirements. Among them, Example 1 demonstrates the most outstanding performance, with a tensile strength of 2.85 MPa, an elongation of 358%, a viscosity of 140 KU, a surface roughness Ra of only 7.2 μm, a crack grade of 5 (no cracks on the surface), and a pattern three-dimensionality of 2.5 mm, achieving the best balance between pattern shaping ability, elastic crack resistance, and surface smoothness.

[0038] Example 1 has the best performance because its weight ratio of hydroxyethyl cellulose to lithium-based bentonite is 1:1, and the weight ratio of polyurethane associative thickener to hydrophobically modified associative alkali-swellable thickener is 1:1, both of which are within the optimal ratio range defined in claims 2 and 3. Furthermore, the amounts of 280 parts of acrylic elastic emulsion and 560 parts of quartz powder are both within the middle value of the preferred range defined in claim 4, and the synergistic effect of each component reaches the optimal state.

[0039] As can be seen from the data in Table 2, the overall performance of Examples 4 and 5 is significantly better than that of Examples 2 and 3. Specifically, Example 4 has a tensile strength of 2.52 MPa, an elongation of 315%, a surface roughness Ra of 10.5 μm, and a crack grade of 4; Example 5 has a tensile strength of 2.48 MPa, an elongation of 308%, a surface roughness Ra of 11.2 μm, and a crack grade of 4; while Example 2 has a tensile strength of only 2.15 MPa, an elongation of 265%, a surface roughness Ra of 14.5 μm, and a crack grade of 3; Example 3 has a tensile strength of 2.28 MPa, an elongation of 278%, a surface roughness Ra of 13.8 μm, and a crack grade of 3.

[0040] Analysis of the causes: In Examples 4 and 5, the weight ratios of hydroxyethyl cellulose to lithium-based bentonite were 1:0.6 and 1:1.6, respectively, and the weight ratios of polyurethane associative thickener to hydrophobically modified associative alkali-swellable thickener were 1:0.5 and 1:1.5, respectively. These ratios are all within the preferred ranges defined in claims 2 and 3. Furthermore, the amounts of acrylic elastic emulsion and quartz powder are both within the preferred range of claim 4, indicating good synergistic effects among the components and thus excellent performance. However, in Example 2, the weight ratio of hydroxyethyl cellulose to lithium-based bentonite was 1:0.54, and the weight ratio of polyurethane associative thickener to hydrophobically modified associative alkali-swellable thickener was 1:3, both exceeding the preferred ranges defined in claims 2 and 3. Similarly, in Example 3, the corresponding ratios were 1:1.87 and 1:0.33, also exceeding the preferred ranges. When the ratio exceeds the preferred range, the synergistic effect of hydroxyethyl cellulose and lithium-based bentonite weakens, the rheological coverage of the dual thickening system is incomplete, and the emulsion network does not adequately encapsulate the powder, all of which lead to a decrease in pattern shaping ability, an increase in surface roughness, and an increase in the risk of cracking.

[0041] Select test samples corresponding to the above comparative examples 1-5, and record the average test results in Table 3 below.

[0042] Table 3: Performance Test Results of Comparative Examples 1-5

[0043] As can be seen from Table 3, the tensile strength of Comparative Example 1 decreased to 1.85 MPa, the elongation decreased to 195%, the surface roughness Ra reached 22.5 μm, the crack grade was only level 2, and the pattern solidity decreased to 1.5 mm.

[0044] Cause Analysis: High-viscosity hydroxyethyl cellulose forms a very strong network structure in water, resulting in excessively high overall viscosity of the coating. Firstly, the excessive viscosity prevents the coating from achieving the necessary fluidity after application, hindering natural leveling and limiting the accumulation and bulging of patterns, leading to flattened patterns and a significant increase in surface roughness. Secondly, during the drying stage, as moisture evaporates, the high-viscosity network generates excessive shrinkage stress. Due to the excessive viscosity of the system, this stress cannot be released through flow, directly tearing the coating and causing severe cracking. Simultaneously, the high viscosity severely hinders the fusion of acrylic elastic emulsion particles, resulting in incomplete film formation and a loose internal structure, directly causing a significant decrease in the tensile strength and elongation of the coating. This demonstrates the necessity of using low-viscosity hydroxyethyl cellulose to ensure leveling, film integrity, and crack resistance.

[0045] The difference between Comparative Example 2 and Example 1 is that lithium-based bentonite was replaced with sodium-based bentonite. As can be seen from Table 3, Comparative Example 2 has a viscosity as high as 152 KU, a surface roughness Ra as high as 25.8 μm, a crack grade of only 2, and a pattern solidity of only 1.6 mm.

[0046] Analysis of causes: Sodium-based bentonite has a much higher water absorption rate and expansion ratio than lithium-based bentonite, resulting in excessively high coating viscosity and difficult construction; at the same time, the gel structure formed by sodium-based bentonite is more rigid, making the coating surface rough and uneven in pattern, and prone to cracking during the drying process. This proves the necessity of lithium-based bentonite in this invention.

[0047] The difference between Comparative Example 3 and Example 1 is that only polyurethane associative thickener was used, and hydrophobically modified associative alkali-swellable thickener was not used. As can be seen from Table 3, the viscosity of Comparative Example 3 was reduced to 125 KU, the surface roughness Ra was 18.5 μm, and the pattern solidity was only 2.1 mm.

[0048] Cause analysis: When using only polyurethane associative thickener, the viscosity of the coating is insufficient at low and medium shear rates, and the pattern partially collapses under gravity, resulting in a decrease in the three-dimensionality of the pattern; at the same time, although the high shear leveling properties are good, the lack of support at low and medium shear rates also affects the surface smoothness.

[0049] The difference between Comparative Example 4 and Example 1 is that only a hydrophobically modified associative alkali-swellable thickener was used, and no polyurethane associative thickener was used. As can be seen from Table 3, the viscosity of Comparative Example 4 was reduced to 122 KU, the surface roughness Ra was 19.2 μm, and the texture solidity was only 1.7 mm.

[0050] Cause analysis: When only hydrophobically modified associative alkali-swellable thickener is used, the viscosity of the coating is insufficient at high shear rates, resulting in poor leveling properties during construction and a rough surface. At the same time, although the thickener has a strong ability to set patterns, it lacks high shear leveling properties, resulting in an uneven pattern surface. The comparison between Comparative Example 3 and Comparative Example 4 proves the necessity of the synergistic effect of the dual thickening system.

[0051] The difference between Comparative Example 5 and Example 1 is that the timing of adding the acrylic elastic emulsion was adjusted to be after the addition of titanium dioxide and quartz powder. As can be seen from Table 3, the surface roughness Ra of Comparative Example 5 is 16.8 μm, and the appearance of the paint film is uneven and has particles.

[0052] Cause analysis: When acrylic elastic emulsion is added after pigments and fillers, the pigments and fillers have already dispersed in the base slurry, but the lack of wetting assistance from the emulsion reduces the dispersion efficiency, and some pigments and fillers agglomerate to form particles; at the same time, the late addition of the emulsion causes a sudden change in the viscosity of the system, affecting the mixing uniformity. This proves the necessity of the reverse dispersion process of adding acrylic elastic emulsion after the defoamer and before the pigments and fillers.

[0053] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. An elliptical large-flower textured coating, characterized in that: By weight, the raw material composition includes: 80-120 parts water; Hydroxyethyl cellulose 1.5-4 parts; 1.5-4 parts lithium-based bentonite; 3-8 parts dispersant; 4-10 parts of defoamer; 240-320 parts of acrylic elastic emulsion; 8-12 parts titanium dioxide; 480-640 parts of quartz powder; 3-8 parts of film-forming aid; 15-30 parts of ethylene glycol; Neutralizing agent 1-4 parts; 1-3 parts of polyurethane associative thickener; 1-3 parts of hydrophobically modified associative alkali-swellable thickener; Preservative 1-5 parts; The viscosity of the hydroxyethyl cellulose is 300-700 mPa·s.

2. The elliptical large-flower textured coating according to claim 1, characterized in that, The weight ratio of hydroxyethyl cellulose to the lithium-based bentonite is 1:0.6-1.

6.

3. The elliptical large-flower textured coating according to claim 1, characterized in that, The weight ratio of the polyurethane associative thickener to the hydrophobic modified associative alkali-swellable thickener is 1:0.5-1.

5.

4. The elliptical large-flower textured coating according to claim 1, characterized in that, The acrylic elastic emulsion comprises 260-300 parts by weight; the quartz powder comprises 520-600 parts by weight.

5. The elliptical large-flower textured coating according to claim 1, characterized in that, The film-forming aid is selected from any one of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, dipropylene glycol butyl ether, and propylene glycol phenyl ether.

6. The elliptical large-flower textured coating according to claim 1, characterized in that, The dispersant is selected from any one of polycarboxylate dispersants, polyacrylate dispersants, and acrylic-maleic anhydride copolymer salt dispersants.

7. The method for preparing the elliptical large-flower textured coating according to any one of claims 1-6, characterized in that, Includes the following steps: S1. Mix water, hydroxyethyl cellulose and lithium-based bentonite to form a basic slurry; S2. Under stirring, add dispersant, first part defoamer accounting for 50-70% of the total amount of defoamer, acrylic elastic emulsion, titanium dioxide and quartz powder to the base slurry, and disperse at 1800-2500 r / min for 18-22 min. S3. Adjust the stirring speed to 800-1200 r / min, and add the film-forming aid and ethylene glycol; S4. Add the neutralizing agent while stirring to adjust the pH; S5. Add the remaining amount of the second part of the defoamer and disperse and defoam at 800-1200 r / min for 3-7 min. S6. Add polyurethane associative thickener and hydrophobically modified associative alkali-swellable thickener, and stir at 800-1200 r / min for 8-12 min. S7. Add preservative, stir and mix for 2-3 minutes, cool to 25℃, and obtain the elliptical large-flower textured coating.

8. The preparation method according to claim 7, characterized in that, The acrylic elastic emulsion is added after the first portion of the defoamer is added and before the titanium dioxide is added.